Adaptasi Dan Pengaruh Budaya Hukum di Indonesia - Arifin, Zainal; Andriyadi, Andriyadi; Fajar, Samson (Muhammadiyah Law Review Journal, 2024)
This study analyzes various aspects that affect legal changes in the sociocultural context in Indonesia. Legal changes are often influenced by the social and cultural dynamics that develop in society. This study aims to understand how social and cultural factors such as traditional values, social norms, and customary customs affect the formation, application, and change of laws in Indonesia. The method used in this study is qualitative with a case study approach, which involves analysis of various legal sources, academic literature, and interviews with legal experts and community leaders. The results of the study show that the interaction between law and socio-cultural aspects creates a continuous adaptation process, where the law must be responsive to changes in values and norms that exist in society. In addition, the findings of this study also indicate that the active involvement of the community in the legislative process